2014
DOI: 10.1093/cesifo/ifu010
|View full text |Cite
|
Sign up to set email alerts
|

Rising Inequality and Intergenerational Mobility: The Role of Public Investments in Human Capital

Abstract: One consequence of the rise in inequality witnessed over the past 40 years is its potentially negative impact on intergenerational mobility if parents at the bottom of the income distribution invest significantly less in their children's human capital. I consider whether public investments in children can potentially offset the inequality of private investments. Specifically, examining changes in public spending in 25 Organization for Economic Co-operation and Development countries over the period 2000–2009, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…These data show that moving to a better neighborhood will result, for the same child, parents, and family income, in long-term higher SES in proportion to the amount of time spent in the better neighborhood. An investigation of whether public spending in 25 countries affected test scores among teens found that increased public spending on health, housing, education, and family support resulted in less inequality in test scores and less of an emphasis on family background in determining these achievement outcomes (Aizer, 2014). The key to the effects observed above is, the earlier the intervention, the better the outcome.…”
Section: Recommendations For Narrowing the Socioeconomic Achievement Gapmentioning
confidence: 99%
“…These data show that moving to a better neighborhood will result, for the same child, parents, and family income, in long-term higher SES in proportion to the amount of time spent in the better neighborhood. An investigation of whether public spending in 25 countries affected test scores among teens found that increased public spending on health, housing, education, and family support resulted in less inequality in test scores and less of an emphasis on family background in determining these achievement outcomes (Aizer, 2014). The key to the effects observed above is, the earlier the intervention, the better the outcome.…”
Section: Recommendations For Narrowing the Socioeconomic Achievement Gapmentioning
confidence: 99%
“…Low birth weight infants born into low-SES families face a particularly steep uphill climb to achieve outcome equality. Fortunately, prior research has shown that both public and private investment can improve outcomes by alleviating credit constraints, improving access to health or education services, and reducing stress (Almond and Currie, 2011;Aizer, 2014;Akee et al, 2018;Currie and Rossin-Slater, 2015;Jones, Milligan, and Stabile, 2015;Aizer et al, 2016;Almond, Currie and Duque, 2017). In this paper we study a particularly vulnerable population-infants born at very low birth weights, below 1200 grams, to mothers with a high school degree or less.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the cross country association between income inequality and intergenerational mobility has been investigated extensively (e.g. Aizer, 2014;Andrews and Leigh, 2009;Björklund and Jäntti, 2012;Blanden, 2013;Brunori et al, 2013;Checchi et al, 1999;Corak, 2013b,a;Holter, 2015;Jerrim and Macmillan, 2015), within-country evidence is still rare on this point. The influential works by Chetty et al (2014b,a) use administrative data on income to estimate intergenerational mobility trends across geographical areas in the US.…”
Section: Inequality and Intergenerational Mobility: The State Of The Artmentioning
confidence: 99%